CYTOKININ RESPONSE FACTOR2 (CRF2) and CRF3 Regulate Lateral Root Development in Response to Cold Stress in Arabidopsis. Issue 8 (18th July 2016) - Jeon, Jin; Cho, Chuloh; Lee, Mi Rha; Van Binh, Nguyen; Kim, Jungmook
Abstract : CRF2 and CRF3, encoding APETALA2 transcription factors, play an important role in lateral root initiation and root system architecture changes under cold stress. Abstract: Lateral roots (LRs) are a major determinant of the root system architecture in plants, and developmental plasticity of LR formation is critical for the survival of plants in changing environmental conditions. In Arabidopsis thaliana, genetic pathways have been identified that regulate LR branching in response to numerous environmental cues, including some nutrients, salt, and gravity. However, it is not known how genetic components are involved in the LR adaptation response to cold. Here, we demonstrate that CYTOKININ RESPONSE FACTOR2 ( CRF2 ) and CRF3, encoding APETALA2 transcription factors, play an important role in regulating Arabidopsis LR initiation under cold stress. Analysis of LR developmental kinetics demonstrated that both CRF2 and CRF3 regulate LR initiation. crf2 and crf3 single mutants exhibited decreased LR initiation under cold stress compared with the wild type, and the crf2 crf3 double mutants showed additively decreased LR densities compared with the single mutants. Conversely, CRF2 or CRF3 overexpression caused increased LR densities. CRF2 was induced by cold via a subset of the cytokinin two-component signaling (TCS ) pathway, whereas CRF3 was upregulated by cold via TCS -independent pathways. Our results suggest that CRF2 and CRF3 respond to cold via TCS-dependent and TCS-independent pathways and control LR initiation and development, contributing to LR adaptation to cold stress.